My city speaks - Lebeuf, Darren (Kids Can Press, 2021)
"A young girl explores her city with her father, taking in all its sensory details. Her city speaks to her in so many ways: "sometimes it echoes," and "sometimes it trills." It "buzzes and tweets and flocks." It's both "busy" and "relaxed," and "smelly" and "sweet." In the end, we discover that the city doesn't just speak to this inquisitive young girl - it also listens ... Author Darren Lebeuf, an award-winning photographer, uses spare text and a rhythmic style to create an evocative read-aloud. The vivid adjectives, both concrete and abstract, will inspire children to try to capture in words what they notice not only in their own town or city, but in any setting. The bright, richly colored cut-paper collage illustrations by Ashley Barron add a captivating visual texture and depth to the story. The portrayal of a girl with a visual impairment walking through the city on her way to her violin recital offers a character education lesson in adaptability."--